The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1117/1.oe.55.4.046110
|View full text |Cite
|
Sign up to set email alerts
|

Studies on effects of feedback delay on the convergence performance of adaptive time-domain equalizers for fiber dispersive channels

Abstract: Abstract. Adaptive time-domain equalizer (TDE) is an important module for digital optical coherent receivers. From an implementation perspective, we analyze and compare in detail the effects of error signal feedback delay on the convergence performance of TDE using either least-mean square (LMS) or constant modulus algorithm (CMA). For this purpose, a simplified theoretical model is proposed based on which iterative equations on the mean value and the variance of the tap coefficient are derived with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…ey show that the RLS has the superior convergence properties. e authors of [23] considered the effects of error feedback delay, using CMA, on the performance of the coherent receiver in the presence of CD. e work done in [24] shows how pipelining and efficient implementation of the adaptive filter's feedback loop in the receiver help reducing the delay of the error signal used in the LMS tap weight updates by 18%.…”
Section: Overview Of Adaptive Filters In Optical Coherent Receiversmentioning
confidence: 99%
“…ey show that the RLS has the superior convergence properties. e authors of [23] considered the effects of error feedback delay, using CMA, on the performance of the coherent receiver in the presence of CD. e work done in [24] shows how pipelining and efficient implementation of the adaptive filter's feedback loop in the receiver help reducing the delay of the error signal used in the LMS tap weight updates by 18%.…”
Section: Overview Of Adaptive Filters In Optical Coherent Receiversmentioning
confidence: 99%
“…It has been shown that frequency-domain (FD) equalization, utilizing the fast Fourier transform (FFT), is more efficient than time-domain (TD) implementation [6][7][8][9][10]. However, in a practical real-time implementation of an adaptive equalizer with block-based processing, filter update delays will be induced due to the FFTs and other DSP operations in the feedback loop, which can degrade the equalizer's tracking ability, particularly during rapid SOP fluctuations [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%